The impact of a technological intervention program on learning mathematical skills - Cóndor-Herrera, Omar (2021)
Learning mathematics is a challenge in the current educational context. This is demonstrated by a high percentage of students who both fail to develop these numerical-type skills and have a low academic performance. This research performs a quasi-experiment to develop mathematical skills and knowledge. The sample consisted of 54 students (20 female and 34 male) between 10 and 14 years old (Mage = 11.11, SD =.79) organized into two groups. First, an experimental group (N = 26) that received a technological intervention of learning virtual objects and second, a control group (N = 28). The results shown a statistical significant interaction between the experimental group and the post-test, which suggests that the intervention improves the skills to solve root exercises F(1, 52) = 10.41, p =.002, η2 =.17, with a significant main effect F(1, 52) = 1184.02, p = <.001, η2 =.96. The knowledge of root exercises problem-solving variable has no meaningful interaction with the intervention F(1, 52) = 2.14, p =.15, η2 =.04. Nevertheless, there was a direct effect between the pre- and post-test measurement differences and the intragroup factor F(1, 52) = 17.95, p = <.001, η2 =.26. The results are discussed about the benefit generated by the use of virtual learning objects in favor of developing mathematical skills and based on previously published studies.